PENGARUH MARKET ORIENTATION DAN IN-STORE CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION DI RATU PAKSI SEMARANG - Kinanti Puspitaningrum; Tiwi Renita Anggraeini; M. Rifki Bakhtiar; Erawati Kartika (STIE PEMBANGUNAN TANJUNGPINANG, 2026)
This study aims to determine the effect of market orientation and in-store customer experience on customer satisfaction at Ratu Paksi Semarang. This research employed a quantitative method with data collection conducted through questionnaires distributed to customers of Ratu Paksi Semarang. The sampling technique used purposive sampling with a total sample of 179 respondents. Data analysis was carried out using multiple linear regression analysis with the assistance of SPSS 2025 Statistics. The results showed that market orientation and in-store customer experience have a positive and significant effect on customer satisfaction. Market orientation helps companies understand customer needs and adjust marketing strategies according to market developments and customer expectations. In addition, a positive in-store customer experience can create comfort and improve customer satisfaction. Simultaneously, both independent variables contributed 59.7% to customer satisfaction, while the remaining percentage was influenced by other variables outside this study. Therefore, companies need to improve market orientation and create positive shopping experiences to enhance customer satisfaction at Ratu Paksi Semarang.